A new primate community from the earliest Oligocene of the Atlantic margin of Northwest Africa: Systematic, paleobiogeographic and paleoenvironmental implications - (:unkn) unknown (My University, 2024)
We report a new Paleogene primate community discovered in the uppermost part of the Samlat Formation outcropping on the continental shore of the Rio de Oro, east of the Dakhla peninsula (in the south of Morocco, near the northern border of Mauritania). Fossils consist of isolated teeth, which were extracted by wet screening of estuarine sediments (DAK C2) dating from the earliest Oligocene (ca. 33.5 Ma). These dental remains testify to the presence of at least eight primate species, documenting distinct families, four of which are among the Anthropoidea (Oligopithecidae [Catopithecus aff. browni], Propliopithecidae [?Propliopithecus sp.], Parapithecidae [Abuqatrania cf. basiodontos], and Afrotarsiidae [Afrotarsius sp.]) and four in the Strepsirrhini (a Djebelemuridae [cf. ‘Anchomomys’ milleri], a Galagidae [Wadilemur cf. elegans], a possible lorisiform [Orogalago saintexuperyi gen. et sp. nov.], and a strepsirrhine of indeterminate affinities [Orolemur mermozi gen. et sp. nov.]). This record of various primates at Dakhla represents the first Oligocene primate community from Northwest Africa, especially from the Atlantic margin of that landmass. Considering primates plus rodents (especially hystricognaths), the taxonomic proximity at the generic (even specific) level between DAK C2 (Dakhla) and the famous Egyptian fossil-bearing localities of the Jebel Qatrani Formation (Fayum Depression), either dating from the latest Eocene (L-41) or from the early Oligocene, suggests the existence of an east-west ‘trans-North African’ environmental continuum during the latest Eocene–earliest Oligocene time interval. The particularly diverse mammal fauna from DAK C2, recorded within the time window of global climate deterioration characterizing the Eocene/Oligocene transition, suggests that this tropical region of northwest Africa was seemingly less affected, if at all, by the cooling and associated paleoenvironmental and biotic changes documented at that ti
Keywords: African Research